ANALISIS PEMASARAN KARET PETANI EKS UPP TCSDP DI DESA HIDUP BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Purba, Reno A; Tety, Ermi; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Agriculture is one of the leading sectors of developing countries. Indonesia is a developing country that relies on plantation as foreign exchange is based on the primary sector. Rubber is one of the strategic commodities fo foreign exchange. This is evident from the history of Indonesian rubber that had become the nomber one producer of rubberr in the world. But after the reorfm era, Indonesian rubber collapsed due to low demand for rubber. This raisesa number of controversies on the marketing of the national rubber.The purposes of this research is to analyse market structure on rubber smallholders plantationof Ex UPP TCSDP in Hidup BaruVillage of Kampar Kiri Tengah District of Kampar Regency. This research started from June 2015 till March 2016. The research method who used in this research is survey method. Data was collected on 31rubber farmers by purposive sampling technique, 6Village Merchantsby purposive sampling technique,3 Medan Wholesalers by purposive sampling technique and Bridgestone’s Factory by Snowball Sampling. The research results shows there is a rubber marketing channel which are Smallholder Plantation- Village Merchant – Medan Wholesaler - Factory. Market structure at rubber marketing of Ex UPP TCSDP imperfectly competitive market leads to oligopsony. Keywords: TCSDP, marketing channel, market structure. Farmer, Agricultur Marketing